Cost Benefit Analysis of North Sindh’s traditional red brick kilns - Siraj Narejo,; Prof. Dr.Muhammad Saleem Rahpoto,; Dr. Azad Khatyan,; Amir Mustafa, (Al-Qanṭara, 2023)
Cost Benefit Analysis is economic evaluation with aim to make strategic decisions for kilns. There are two types of the costs i.e. fixed and variable costs Variable cost is 27%, 16% and 12 % of total cost of goods sold(COGS) for small, medium and large kilns. COGS is the final kiln cost. Largest cost for all small and medium kilns is labour cost (36-40%) of the COGS. For large kilns it is fuel cost (39%).Second largest cost for small kilns is FOH (17%), for medium kilns fuel(34%) and for large kilns labour costs(36%). . Least cost for small kilns is clay (3%), for medium kilns water cost (0.9%) and for large kilns water cost (0.4%). On the average Direct Labour is 45 % of the prime cost. It takes a lot of cost to convert clay into bricks for small kilns i.e. 63% of total cost. On the average cost of goods available for sale (COGAS) is 3.3% more than final cost (COGS) for large kilns, 9.3% for medium kilns and 14.1 % for small kilns. Some difference results between COGAS and final cost results are in negative percentage because final cost is higher than COGAS. Some kilns have zero difference between COGS and COGAS. Cost of one brick is largest for small kilns i.e. 4.84 Rs, for medium it is 4.86 Rs and 4.52 Rs for large kilns . Cost of one brick is highest in sukkur (4.9Rs) but least in Larkana (4.4Rs). Brick price is highest in Khairpur (7.05Rs) and least price in sukkur(6.9Rs). There is positive and significant relationship between cost and price of a brick made at an average kiln at adjusted R2 value of 0.083. Y Intercept tells that if the cost of making one brick falls to zero the brick price will remain 6.186Rs. Unit Contribution Margin(CM) ratio is 41%,45% and 51% for large, medium and small kilns respectively. For every rupee sales only 41% goes to covering FC and profit generation for large kilns. Higher the ratio better it is. It means more money available to cover FC. Breakeven Point Sales (BEP) is 150841 bricks (1043289Rs), 1338155 bricks (9374469 Rs) and 3839411 bricks (27279716Rs) sale for small , medium and large kilns respectively. On the average operating expenses are 2.9 times non operating expenses for brick kiln industry. When non operating expenses are subtracted from EBIT we get Net Profit for a kiln. Net profit is 281808, 3647403 and 14908971 Rs for small , medium and large kilns calculated in income statement. Net profit , as percentage of gross profit, is highest for large kilns (80%). It is 50%, 68% for small and medium kilns. Kiln size determines Net profit. Net profit is least for small kilns i.e. 50% of Gross profit. Net profit is less than gross profit because of operating expenses and non operating expenses. Benefit Cost Ratio is 0.27 for small kilns, 0.35 for medium kilns, and 0.52 for large kilns. Finding the biggest impact of a cost type on kiln’s net profit is important. Multiple linear regression is performed with five variables ie. Prime Cost, conversion cost , cost of goods manufacturing (COGM), COGAS and COGS. Y variable is Net Profit. All the variables are significant except for intercept. COGM and COGAS are both inversely related to net profit. If they decrease net profit will increase. But COGS is positively related to Net Profit. The strongest relation is that of COGM with Net Profit. Adjusted R2is 0.863.